2013
DOI: 10.1139/l2012-032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of column and superstructure stiffness on the seismic response of bridges in the transverse direction

Abstract: The transverse seismic responses of continuous 4-span bridges designed based on the 2006 Canadian Highway Bridge Design Code were studied using inelastic time history analyses. A total of 648 bridge configurations were considered in which the column heights, column diameters, superstructure stiffness and mass as well as abutment restraint conditions were studied. The maximum ductility demands obtained using elastic and inelastic analyses were compared to study the influence of the degree of irregularity. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Therefore, these modelling assumptions were adopted for the seismic analysis and evaluation of the bridges in this research. More details concerning the modelling of the bridges and the verification of computer models are available in [1,12,[22][23][24]. bridges in this research.…”
Section: Bridge Properties and Modellingmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, these modelling assumptions were adopted for the seismic analysis and evaluation of the bridges in this research. More details concerning the modelling of the bridges and the verification of computer models are available in [1,12,[22][23][24]. bridges in this research.…”
Section: Bridge Properties and Modellingmentioning
confidence: 99%
“…bridges in this research. More details concerning the modelling of the bridges and the verification of computer models are available in [1,12,[22][23][24]. The modal properties of the bridges including the fundamental transverse mode, TT, second transverse mode, TT2, fundamental longitudinal period, TL, geometric mean period, TG, (defined as TG = (TL•TT) 0.5 ) and the effective modal mass ratios are presented in Table 1.…”
Section: Bridge Properties and Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…ey concluded that when the deck is stiff enough to control pier displacements, and the distribution of pier's stiffness is symmetric, the proposed criterion offers reasonable accuracy. Several studies served the relative stiffness of deck to piers as an indicator of bridge irregularity [9,10]. Akbari and Maalek carried out an exhaustive comparison between different regularity indices [11].…”
Section: Introductionmentioning
confidence: 99%